2019
DOI: 10.1021/acscatal.9b04813
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Depolymerization of Native Lignin Enabled by Proton-Coupled Electron Transfer

Abstract: Here we report a catalytic, light-driven method for the redox-neutral depolymerization of native lignin biomass at ambient temperature. This transformation proceeds via a proton-coupled electron-transfer (PCET) activation of an alcohol O-H bond to generate a key alkoxy radical intermediate, which then drives the β-scission of a vicinal C-C bond. Notably, this depolymerization is driven solely by visible light irradiation, requiring no stoichiometric chemical reagents and producing no stoichiometric waste. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 41 publications
0
71
0
Order By: Relevance
“…A proton‐coupled electron transfer (PCET) process was also reported for the cleavage of C−C bonds in lignin β‐O‐4 linkages . PCET refers to the reaction in which protons and electrons are transferred at the same time.…”
Section: Pathways and Mechanisms Of Photocatalytic Lignin Conversionmentioning
confidence: 99%
“…A proton‐coupled electron transfer (PCET) process was also reported for the cleavage of C−C bonds in lignin β‐O‐4 linkages . PCET refers to the reaction in which protons and electrons are transferred at the same time.…”
Section: Pathways and Mechanisms Of Photocatalytic Lignin Conversionmentioning
confidence: 99%
“…The PCET strategy described here for C-C bond scission was adapted independently by the groups of Zhang and Knowles for the depolymerization of lignin models and biomass-derived polymeric lignin. 88,89 Following their 2019 report, the Knowles lab developed a strategy for the catalytic ring expansion of cyclic alcohols to n + 1 or n + 2 expanded ketones by taking advantage of the propensity of alkoxy radicals to undergo C-C cleavage. 90 By employing a similar series of elementary steps as in their prior work, O-H PCET is leveraged to generate an alkoxy radical intermediate from cyclic allylic alcohols (Scheme 32).…”
Section: Proton-coupled Electron Transfermentioning
confidence: 99%
“…With the success of model substrate 1, we found that a range of other 1,2-disubstituted olefins gave excellent yields of the desired cyclic ether products (3)(4)(5)(6)(7)(8)(9). Hydroetherification of disubstituted olefins with secondary alcohols also proved to be viable, albeit with moderate reactivity (10). Notably, this method provides direct access to a variety of bicyclic structures from alcohol precursors, forming fused rings (11,12) and bridged ethers (13) with high diastereoselectivity.…”
mentioning
confidence: 96%
“…Our group has developed methods for the homolytic activation of alcohol O À H bonds to access alkoxy radical intermediates, focusing exclusively on CÀC bond bscission reactions. [10,11] Because the rates of b-scission and 1,5hydrogen atom transfer (1,5-HAT) are often comparable to the rate of cyclization, [12, 8b,i] we wondered whether alkoxy radicals could be leveraged instead for productive CÀO bond formation, thereby generating cyclic ethers directly from readily accessible alkenols while outcompeting other pathways. [13] Within this context, we endeavored to find catalysts and reaction conditions that could not only effectively bias the reactivity of alkoxy radicals to favor olefin addition but to do so with a broad scope and functional-group tolerance.…”
mentioning
confidence: 99%
See 1 more Smart Citation